Ablation of Protein Kinase CK2β in Skeletal Muscle Fibers Interferes with Their Oxidative Capacity - Eiber, Nane; Simeone, Luca; Hashemolhosseini, Said (Pharmaceuticals, 2017)
The tetrameric protein kinase CK2 was identified playing a role at neuromuscular junctions by studying CK2β-deficient muscle fibers in mice, and in cultured immortalized C2C12 muscle cells after individual knockdown of CK2α and CK2β subunits. In muscle cells, CK2 activity appeared to be at least required for regular aggregation of nicotinic acetylcholine receptors, which serves as a hallmark for the presence of a postsynaptic apparatus. Here, we set out to determine whether any other feature accompanies CK2β-deficient muscle fibers. Hind limb muscles gastrocnemius, plantaris, and soleus of adult wildtype and CK2β-deficient mice were dissected, cross-sectioned, and stained histochemically by Gomori trichrome and for nicotinamide adenine dinucleotide (NADH) dehydrogenase and succinate dehydrogenase (SDH) enzymatic activities. A reduction of oxidative enzymatic activity was determined for CK2β-deficient muscle fibers in comparison with wildtype controls. Importantly, the CK2β-deficient fibers, muscle fibers that typically exhibit high NADH dehydrogenase and SDH activities, like slow-type fibers, showed a marked reduction in these activities. Altogether, our data indicate additional impairments in the absence of CK2β in skeletal muscle fibers, pointing to an eventual mitochondrial myopathy.
EVALuna2:33489

Collagen VI is required for the structural and functional integrity of the neuromuscular junction - Cescon, Matilde; Gregorio, Ilaria; Eiber, Nane; Borgia, Doriana; Fusto, Aurora; Sabatelli, Patrizia; Scorzeto, Michele; Megighian, Aram; Pegoraro, Elena; Hashemolhosseini, Said; Bonaldo, Paolo (Acta Neuropathologica, 2018)
The synaptic cleft of the neuromuscular junction (NMJ) consists of a highly specialized extracellular matrix (ECM) involved in synapse maturation, in the juxtaposition of pre- to post-synaptic areas, and in ensuring proper synaptic transmission. Key components of synaptic ECM, such as collagen IV, perlecan and biglycan, are binding partners of one of the most abundant ECM protein of skeletal muscle, collagen VI (ColVI), previously never linked to NMJ. Here, we demonstrate that ColVI is itself a component of this specialized ECM and that it is required for the structural and functional integrity of NMJs. In vivo, ColVI deficiency causes fragmentation of acetylcholine receptor (AChR) clusters, with abnormal expression of NMJ-enriched proteins and re-expression of fetal AChRγ subunit, both in Col6a1 null mice and in patients affected by Ullrich congenital muscular dystrophy (UCMD), the most severe form of ColVI-related myopathies. Ex vivo muscle preparations from ColVI null mice revealed altered neuromuscular transmission, with electrophysiological defects and decreased safety factor (i.e., the excess current generated in response to a nerve impulse over that required to reach the action potential threshold). Moreover, in vitro studies in differentiated C2C12 myotubes showed the ability of ColVI to induce AChR clustering and synaptic gene expression. These findings reveal a novel role for ColVI at the NMJ and point to the involvement of NMJ defects in the etiopathology of ColVI-related myopathies.
EVALuna2:35740

Lack of Desmin in Mice Causes Structural and Functional Disorders of Neuromuscular Junctions - Eiber, Nane; Fröb, Franziska; Schowalter, Mirjam; Thiel, Christian; Clemen, Christoph S.; Schröder, Rolf; Hashemolhosseini, Said (Frontiers in Molecular Neuroscience, 2020)
Desmin, the major intermediate filament (IF) protein in muscle cells, interlinks neighboring myofibrils and connects the whole myofibrillar apparatus to myonuclei, mitochondria, and the sarcolemma. However, desmin is also known to be enriched at postsynaptic membranes of neuromuscular junctions (NMJs). The pivotal role of the desmin IF cytoskeletal network is underscored by the fact that over 120 mutations of the human DES gene cause hereditary and sporadic myopathies and cardiomyopathies. A subgroup of human desminopathies comprises autosomal recessive cases resulting in the complete abolition of desmin protein. In these patients, who display a more severe phenotype than the autosomal dominant cases, it has been reported that some individuals also suffer from a myasthenic syndrome in addition to the classical occurrence of myopathy and cardiomyopathy. Since further studies on the NMJ pathology are hampered by the lack of available human striated muscle biopsy specimens, we exploited homozygous desmin knock-out mice which closely mirror the striated muscle pathology of human patients lacking desmin protein. Here, we report on the impact of the lack of desmin on the structure and function of NMJs and the transcription of genes coding for postsynaptic proteins. Desmin knock-out mice display a fragmentation of NMJs in soleus, but not in the extensor digitorum longus muscle. Moreover, soleus muscle fibers show larger NMJs. Further, transcription levels of acetylcholine receptor (AChR) genes are increased in muscles from desmin knock-out mice, especially of the AChR gamma subunit, which is known as a marker of muscle fiber regeneration. Electrophysiological recordings depicted a pathological decrement of nerve-dependent endplate potentials and an increased rise time of the nerve-independent miniature endplate potentials. The latter appears related to the fragmentation of NMJs in desmin knockout mice. Our study highlights the essential role of desmin for the structural and functional integrity of mammalian NMJs.
CRIS-Team WoS Importer:2020-11-27

Loss of Protein Kinase Csnk2b/CK2 beta at Neuromuscular Junctions Affects Morphology and Dynamics of Aggregated Nicotinic Acetylcholine Receptors, Neuromuscular Transmission, and Synaptic Gene Expression - Eiber, Nane; Rehman, Michael; Kravic, Bojana; Rudolf, Ruediger; Sandri, Marco; Hashemolhosseini, Said (Cells, 2019)
The protein kinase Csnk2/CK2 is important for cell proliferation, differentiation, and survival. Previously, we showed that CK2 binds distinctive proteins at neuromuscular junctions (NMJs) of mice and phosphorylates some of them. CK2 likely stabilizes clustered nicotinic acetylcholine receptors (AChRs). In the absence of the beta-subunit of CK2 in skeletal muscle fibers, mice develop an age-dependent decrease of grip strength accompanied by NMJ fragmentation and impairments of neuromuscular transmission. However, the precise role of CK2 beta regarding the clustering of AChRs and downstream signaling at NMJs is unknown. Here, we compared conditional CK2 beta-deficient mice with controls and found in the mutants (1) a lower decrement of endplate potentials after repetitive stimulation and decrements of nerve-evoked compound muscle action potentials decayed more rapidly after synaptic transmission was partially blocked, (2) that their muscle weakness was partially rescued by administration of an acetylcholine esterase inhibitor, (3) fragmented NMJs and impaired AChR clustering was detected in muscles and cultured muscle cells, (4) enlarged myonuclei, (5) impaired synaptic gene expression, and (6) a high turnover rate of their AChR clusters in vivo. Altogether, our data demonstrate a role for CK2 at the NMJ by maintaining a high density of AChRs and ensuring physiological synaptic gene expression.
CRIS-Team WoS Importer:2019-09-24

Methocarbamol blocks muscular Nav1.4 channels and decreases isometric force of mouse muscles - Zhang, Yaxin; Otto, Philipp; Qin, Lu; Eiber, Nane; Hashemolhosseini, Said; Kröger, Stephan; Brinkmeier, Heinrich (Muscle & Nerve, 2020)
Background: The muscle relaxant methocarbamol is widely used for the treatment of muscle spasms and pain syndromes. To elucidate molecular mechanisms of its action, we studied its influence on neuromuscular transmission, on isometric muscle force, and on voltage-gated Na+ channels. Methods: Neuromuscular transmission was investigated in murine diaphragm-phrenic nerve preparations and muscle force studied on mouse soleus muscles. Nav1.4 channels and Nav1.7 channels were functionally expressed in eukaryotic cell lines. Results: Methocarbamol, at 2 mM, decreased the decay of endplate currents, slowed the decay of endplate potentials and reduced tetanic force of soleus muscles. The drug reversibly inhibited current flow through muscular Nav1.4 channels, while neuronal Nav1.7 channels were unaffected. Conclusions: The study provides evidence for peripheral actions of methocarbamol on skeletal muscle. Muscular Na+ channels are a molecular target of methocarbamol. Since Nav1.7 currents were unaffected, methocarbamol is unlikely to exert its analgesic effect by directly blocking Nav1.7 channels.
CRIS-Team Scopus Importer:2020-11-06
Keywords: methocarbamol; muscle force; muscle relaxant; neuromuscular transmission; voltage-gated Na

Neuromuscular endplate pathology in recessive desminopathies: Lessons from man and mice - Durmus, Hacer; Ayhan, Ozgecan; Cirak, Sebahattin; Deymeer, Feza; Parman, Yesim; Franke, Andre; Eiber, Nane; Chevessier, Frederic; Schlötzer-Schrehardt, Ursula; Clemen, Christoph S.; Hashemolhosseini, Said; Schröder, Rolf; et al. (Neurology, 2016)
To assess the clinical, genetic, and myopathologic findings in 2 cousins with lack of desmin, the response to salbutamol in one patient, and the neuromuscular endplate pathology in a knock-in mouse model for recessive desminopathy.We performed clinical investigations in the patients, genetic studies for linkage mapping, exome sequencing, and qPCR for transcript quantification, assessment of efficacy of (3-month oral) salbutamol administration by muscle strength assessment, 6-minute walking test (6MWT), and forced vital capacity, analysis of neuromuscular endplate pathology in a homozygous R349P desmin knock-in mouse by immunofluorescence staining of the hind limb muscles, and quantitative 3D morphometry and expression studies of acetylcholine receptor genes by quantitative PCR.Both patients had infantile-onset weakness and fatigability, facial weakness with bilateral ptosis and ophthalmoparesis, generalized muscle weakness, and a decremental response over 10% on repetitive nerve stimulation. Salbutamol improved 6MWT and subjective motor function in the treated patient. Genetic analysis revealed previously unreported novel homozygous truncating desmin mutation c.345dupC leading to protein truncation and consequent fast degradation of the mutant mRNA. In the recessive desminopathy mouse with low expression of the mutant desmin protein, we demonstrated fragmented motor endplates with increased surface areas, volumes, and fluorescence intensities in conjunction with increased ? and ? acetylcholine receptor subunit expression in oxidative soleus muscle.The patients were desmin-null and had myopathy, cardiomyopathy, and a congenital myasthenic syndrome. The data from man and mouse demonstrate that the complete lack as well as the markedly decreased expression of mutant R349P desmin impair the structural and functional integrity of neuromuscular endplates.
EVALuna2:4994